Phenotypic antimicrobial susceptibility of Escherichia coli from raw meats, ready-to-eat meats, and their related samples in one health context - Frederick Adzitey; Nurul Huda; Amir Husni Mohd Shariff (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Meat is an important food source that can provide a significant amount of protein for human development. The occurrence of bacteria that are resistant to antimicrobials in meat poses a public health risk. This study evaluated the occurrence and antimicrobial resistance of E. coli (Escherichia coli) isolated from raw meats, ready-to-eat (RTE) meats and their related samples in Ghana. E. coli was isolated using the USA-FDA Bacteriological Analytical Manual and phenotypic antimicrobial susceptibility test was performed by the disk diffusion method. Of the 200 examined meats and their related samples, 38% were positive for E. coli. Notably, E. coli was highest in raw beef (80%) and lowest in RTE pork (0%). The 45 E. coli isolates were resistant ≥ 50% to amoxicillin, trimethoprim and tetracycline. They were susceptible to azithromycin (87.1%), chloramphenicol (81.3%), imipenem (74.8%), gentamicin (72.0%) and ciprofloxacin (69.5%). A relatively high intermediate resistance of 33.0% was observed for ceftriaxone. E. coli from raw meats, RTE meats, hands of meat sellers and working tools showed some differences and similarities in their phenotypic antimicrobial resistance patterns. Half (51.1%) of the E. coli isolates exhibited multidrug resistance. The E. coli isolates showed twenty-two different resistant patterns, with a multiple antibiotic resistance index of 0.0 to 0.7. The resistant pattern amoxicillin (A, n = 6 isolates) and amoxicillin-trimethoprim (A-TM, n = 6 isolates) were the most common. This study documents that raw meats, RTE meats and their related samples in Ghana are potential sources of antimicrobial-resistant E. coli and pose a risk for the transfer of resistant bacteria to the food chain, environment and humans.